Wear-resistant and mildew-proof ceramic tile and preparation method thereof
By applying a modified interface agent on the ceramic tile and adding antibacterial materials to the glaze layer, the problem of degradation of wear resistance and antibacterial and mildew resistance of the ceramic tile is solved, and the long-term wear resistance and long-lasting antibacterial and mildew resistance of the ceramic tile is achieved.
Patent Information
- Application Number
- CN202411940287.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
The wear resistance and antibacterial and mildew resistance performance of existing ceramic tiles decrease after long-term use, resulting in glaze falling off and loss of function.
By applying a modified interface agent to the ceramic tile body and adding silver-carrying zirconium phosphate and modified titanium dioxide to the glaze layer, a durable antibacterial and anti-mold performance is formed. At the same time, the binding force between the blank and the glaze layer is enhanced by the combination of the modified interface agent and the glaze layer material.
It significantly improves the wear resistance and mildew resistance of the tiles, extends the service life of the tiles, and maintains good antibacterial effect, and does not significantly reduce even after 1500 times of washing.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic tiles, and in particular relates to a wear-resistant and mildew-proof ceramic tile and a preparation method thereof. Background Art
[0002] Ceramic tiles are a kind of building decoration material with rich categories and exquisite patterns. They are often used for indoor and outdoor decoration, especially kitchens, bathrooms, indoor and outdoor floors, etc. Ceramic tiles are generally composed of three parts: body, bottom glaze layer and top glaze layer. The glaze and body interact at high temperature, so that the components in the glaze, especially the alkaline oxides, fully react with the body and penetrate into the body. At the same time, it also promotes the components in the body to enter the glaze layer, forming a body-glaze bonding layer.
[0003] From the use of ceramic tiles, it can be seen that although the use of ceramic tiles greatly improves the aesthetics of the building, the surface coating will be lost due to continuous friction during long-term use, which will reduce its aesthetics. Therefore, wear resistance is an important performance indicator of ceramic tiles. Poor wear resistance not only damages the glaze, but also causes the ceramic tiles to change color, glossiness changes, anti-fouling performance decreases, anti-slip performance changes, etc. after a period of use, which directly affects the decorative effect of the product. At the same time, with the rapid development of the construction industry, the production and consumption of ceramic tiles have achieved great development. At the same time, the performance requirements for ceramic tiles are getting higher and higher. For example, when they are used in special places such as hospitals and schools, ceramic tiles are often required to have certain antibacterial and mildew resistance to reduce the harm to human health. At this time, ceramic tiles with antibacterial and mildew resistance came into being. Antibacterial and mildew-resistant tiles are the product of the combination of ceramic tile technology and antibacterial technology. They can increase the antibacterial and mildew-resistant effects while keeping the original functions of the tiles basically unchanged. The antibacterial and mildew-proof tiles of the related art have raw materials including feldspar, silica fume, quartz, silicate, clay, N-doped titanium dioxide, and metallic silver powder, and the raw materials are mixed, pressed into shape, and fired.
[0004] Chinese patent application CN117049782A discloses a non-slip wear-resistant antibacterial tile and a preparation method thereof. The non-slip wear-resistant antibacterial tile includes a body layer, a glaze layer, a pattern texture layer, a non-slip wear-resistant layer and an antibacterial protective layer from bottom to top. The antibacterial protective layer uses nano zinc oxide and nano copper oxide in a certain proportion as an antibacterial agent; the preparation method of the non-slip wear-resistant antibacterial tile includes the steps of: preparing a body, preparing a glaze slurry, preparing a non-slip wear-resistant slurry, preparing a pattern texture, preparing an antibacterial glaze slurry, and firing to obtain a non-slip wear-resistant antibacterial tile. The non-slip wear-resistant antibacterial tile of the invention has good antibacterial performance, and the antibacterial rate reaches more than 99%. Chinese patent application CN109016098A discloses an antibacterial tile and a preparation method thereof, including a tile body and an antibacterial functional layer, the antibacterial functional layer is located on the surface of the tile body, and the raw materials of the antibacterial functional layer include antibacterial materials and adhesive materials. The antibacterial ceramic tile described in the invention has an antibacterial functional layer adhered to the tiny hole structure of the roughened ceramic tile glaze, which makes the antibacterial functional layer not easy to be worn, greatly improving the service life. The antibacterial material in the invention uses up-conversion fluorescent nanoparticles, which can stimulate ultraviolet light under natural light or indoor light to achieve the antibacterial and sterilization effect. However, the antibacterial layer of the above patents is on the surface of the ceramic tile. After long-term use, the antibacterial coating may fall off due to wear resistance, thereby losing the antibacterial and mildew-proof properties.
[0005] Therefore, it is of great significance to develop a method for preparing wear-resistant and mildew-resistant ceramic tiles in the art to improve the wear resistance and long-term antibacterial and mildew-resistant properties of the ceramic tiles. Summary of the invention
[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a wear-resistant and mildew-proof ceramic tile and a preparation method thereof. The ceramic tile has good mechanical strength and long-lasting wear-resistant and mildew-proof properties and has good application prospects.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A wear-resistant and mildew-proof ceramic tile comprises a body and a glaze layer attached to the body, wherein the wear-resistant and mildew-proof ceramic tile is obtained by first coating the surface of the body with a modified interface agent and then glazing the body;
[0009] Wherein, the glaze layer comprises the following raw materials by weight:
[0010] 40-50 parts of silicon dioxide, 30-35 parts of aluminum oxide, 15-20 parts of modified titanium dioxide, 6-10 parts of barium carbonate, 6-10 parts of mullite, 5-8 parts of silver-loaded zirconium phosphate, 4-8 parts of potassium carbonate, 4-8 parts of sodium carbonate, 3-7 parts of limestone, 3-5 parts of sodium borate, 2-4 parts of zinc oxide, and 0.5-1 parts of sodium tripolyphosphate.
[0011] The green body comprises the following raw materials in parts by weight:
[0012] 40-45 parts of clay, 25-30 parts of kaolin, 15-20 parts of dolomite, 15-20 parts of quartz, 12-17 parts of potassium feldspar, 12-16 parts of red mud, 12-16 parts of mullite, 10-15 parts of diatomaceous earth, 6-9 parts of magnesium oxide, 5-8 parts of calcined talc, 3-4 parts of borax, and 2-3 parts of copper oxide.
[0013] Preferably, the glaze layer comprises the following raw materials, by weight: 45-50 parts of silicon dioxide, 32-35 parts of aluminum oxide, 17-20 parts of modified titanium dioxide, 6-8 parts of barium carbonate, 6-8 parts of mullite, 6-8 parts of silver-loaded zirconium phosphate, 4-6 parts of potassium carbonate, 4-6 parts of sodium carbonate, 4-6 parts of limestone, 3-4 parts of sodium borate, 2-3 parts of zinc oxide, and 0.5-0.8 parts of sodium tripolyphosphate.
[0014] Preferably, the thickness of the glaze layer is 0.3-0.5 mm.
[0015] Preferably, the preparation method of the modified interface agent comprises the following steps:
[0016] Aluminum phosphate is added to the glycerol aqueous solution, followed by sodium dodecyl sulfate, and after stirring evenly, dimethyl allyl malonate, aluminum acetylacetonate, tetrapropyl zirconate, and dibenzoyl peroxide are added, and stirring is continued for 20-30 minutes to obtain the modified interface agent.
[0017] Preferably, the stirring temperature is 30-40° C., the mass fraction of glycerol in the glycerol aqueous solution is 50-60%, and the mass ratio of the aluminum phosphate, glycerol aqueous solution, sodium dodecyl sulfate, dimethyl allyl malonate, aluminum acetylacetonate, tetrapropyl zirconate, and dibenzoyl peroxide is 10-15:130-160:5-9:2-4:6-8:7-11:0.5-0.8.
[0018] In the present invention, the added modified interface agent significantly improves the interface bonding performance between the green body and the glaze layer through the synergistic effect of multiple components, the glycerol aqueous solution is used as the dispersion medium to improve the uniformity and wettability of the coating, so that the interface agent can better penetrate into the tile green body, aluminum phosphate is used as a binder to form a coordination effect with the metal oxide on the surface of the green body, thereby forming a bonding force between the green body and the glaze layer, sodium dodecyl sulfate is used as a surfactant to mix the various components in the raw materials evenly, aluminum acetylacetonate and tetrapropyl zirconate are used as coupling agents to form chemical bonds with the green body and the glaze layer, and form oxides during the sintering process to fill the microscopic pores, so that the glaze layer and the green body have a stronger bonding force.
[0019] Preferably, the preparation method of the modified titanium dioxide comprises the following steps:
[0020] S1. Add calcium carbonate to an ethanol aqueous solution, then add tetrabutyl titanate and ammonia water to carry out a hydrothermal reaction. After the reaction is completed, filter, wash, dry, and roast. Add to a dilute hydrochloric acid solution, soak for 20-30 minutes, then filter, wash, and dry to obtain porous titanium dioxide.
[0021] S2, adding the porous titanium dioxide prepared in step S1 into deionized water, and then adding zinc nitrate, cerium nitrate and zirconium oxychloride, stirring evenly, adding ammonia water to adjust the pH to 9-10, stirring to react, filtering, washing, drying and calcining after the reaction is completed to obtain composite titanium dioxide;
[0022] S3, adding the composite titanium dioxide in step S2 into an ethanol aqueous solution, and then adding vinyltriethoxysilane, reacting at 50-60° C. for 2-3 hours, filtering, washing, and drying after the reaction is completed to obtain modified titanium dioxide.
[0023] Preferably, the volume ratio of ethanol to water in the ethanol aqueous solution in step S1 is 7-8:2-3, the mass ratio of calcium carbonate, tetrabutyl titanate and ammonia water is 30-40:80-90:50-60, the mass fraction of ammonia water is 20-25%, the temperature of the hydrothermal reaction is 120-130°C, the time is 5-8h, and the calcination temperature is 600-700°C, and the time is 1-2h.
[0024] In the present invention, titanium dioxide with a porous structure is first prepared by a hydrothermal method, so that the titanium dioxide has a larger specific surface area and its mechanical bite force with the glaze matrix is enhanced.
[0025] Preferably, in step S2, the mass ratio of porous titanium dioxide, deionized water, zinc nitrate, cerium nitrate and zirconium oxychloride is 100:1000-1200:30-40:15-25:10-20, the stirring reaction temperature is 60-65°C, the time is 3-4h, and the calcination temperature is 500-550°C, and the time is 2-3h.
[0026] In the present invention, zinc, cerium and zirconium elements are then introduced into the porous titanium dioxide by an impregnation method, thereby further improving the wear resistance and mildew resistance of the titanium dioxide.
[0027] Preferably, the mass ratio of the composite titanium dioxide to vinyltriethoxysilane in step S3 is 100:9-14.
[0028] In the present invention, vinyl triethoxysilane is finally used to treat the composite titanium dioxide. On the one hand, the dispersibility of the modified titanium dioxide in the glaze surface can be improved. At the same time, the introduced vinyl forms an initial cross-linked network with the modified interface agent during the heat treatment process. In the subsequent sintering process, the modified titanium dioxide forms a chemical bond with the silicate network in the glaze layer, further improving the wear resistance and adhesion of the glaze layer.
[0029] The present invention also protects a method for preparing the wear-resistant and mildew-proof ceramic tile as described above, comprising the following steps:
[0030] (1) Preparation of ceramic tile blanks: weigh raw materials according to the formula, mix clay, kaolin, dolomite, quartz, potassium feldspar, red mud, mullite, diatomaceous earth, magnesium oxide, calcined talc, borax, and copper oxide evenly, add 35-40% of water by weight of the total ingredients of the blank to prepare a slurry, ball mill for 3-4 hours, sieve, degas, press and form at 40-50 MPa, and then dry at 100-110° C. to obtain ceramic tile blanks;
[0031] (2) preparing glaze layer materials: weighing raw materials according to the formula, mixing silicon dioxide, aluminum oxide, modified titanium dioxide, barium carbonate, mullite, silver-loaded zirconium phosphate, potassium carbonate, sodium carbonate, limestone, sodium borate, zinc oxide, and sodium tripolyphosphate, adding 70-75% of water by weight of the total ingredients of the glaze layer to prepare a glaze slurry, ball milling for 7-9 hours, and passing the glaze slurry through a 325-mesh sieve after milling to obtain a glaze layer material;
[0032] (3) Apply the modified interface agent evenly on the dry tile body, with a coating amount of 100-120g / m 2 , preheat at 50-60℃ for 20-30min, then use the glaze spraying process to spray the prepared glaze layer material on the tile body, and heat treat at 110-120℃ for 40-60min; place the glazed tiles in a roller kiln for sintering, the sintering process is pre-firing at 400-500℃ for 30-40min, then heating to 1150-1200℃ at a rate of 5-8℃ / min, keeping warm for 40-50min, and finally cooling to obtain the wear-resistant and mildew-proof tiles.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The wear-resistant and mildew-proof ceramic tile provided by the present invention achieves excellent wear resistance and mildew-proof effect of the ceramic tile by introducing a modified interface agent of specific composition between the ceramic tile body and the glaze layer, wherein the addition of silver-loaded zirconium phosphate and modified titanium dioxide provides long-lasting antibacterial and mildew-proof performance, and a large number of microscopic uneven surfaces in the modified titanium dioxide, and the inorganic components in the interface agent (such as aluminum phosphate, aluminum acetylacetonate, tetrapropyl zirconate) form oxides during the sintering process, filling the microscopic pores on the surface of the body and titanium dioxide, and significantly enhancing the interface bonding strength through the physical bite effect, thereby improving the long-term wear resistance and mildew-proof of the ceramic tile glaze layer.
[0035] (2) The wear-resistant and mildew-proof ceramic tile provided by the present invention has a modified interface agent added, which significantly improves the interface bonding performance between the body and the glaze layer through the synergistic effect of multiple components. The use of glycerol aqueous solution as a dispersion medium improves the uniformity and wettability of the coating, so that the interface agent can better penetrate into the ceramic tile body. Aluminum phosphate is used as a binder to form a coordination effect with the metal oxides on the surface of the body, and aluminum ions can interact with the oxides in the glaze layer, thereby forming a chemical bridge between the body and the glaze layer. Sodium dodecyl sulfate is added as a surfactant to mix the components in the raw materials evenly. Aluminum acetylacetonate and tetrapropyl zirconate are used as coupling agents to form chemical bonds with the body and the glaze layer, and form oxides during the sintering process to fill the microscopic pores, so that the glaze layer and the body have a stronger bonding force.
[0036] (3) The wear-resistant and mildew-proof ceramic tile provided by the present invention comprises modified titanium dioxide added to the glaze layer material, and then subjected to a calcium carbonate template method and a hydrothermal reaction, followed by a hydrochloric acid impregnation treatment, thereby preparing porous titanium dioxide. The porous structure not only provides a larger specific surface area, but also enhances the mechanical bite force with the glaze matrix. Subsequently, zinc, cerium, and zirconium elements are introduced by an impregnation method for composite modification, thereby improving the wear resistance of the glaze layer. The zinc ions enhance the antibacterial property, the cerium ions enhance the thermal stability, and the zirconium ions improve the mechanical strength. The synergistic effect of the three elements significantly improves the modified titanium dioxide. Comprehensive performance; subsequently, the composite titanium dioxide was modified with vinyltriethoxysilane, which not only improved the compatibility and bonding strength of the glaze matrix, but also the introduced vinyl formed an initial cross-linking network with the modified interface agent during the heat treatment process. In the subsequent sintering process, the modified titanium dioxide formed a chemical bond with the silicate network in the glaze layer, and the metal ions (zinc, cerium, zirconium) on the surface of the modified titanium dioxide promoted the crystal phase transformation of the local area at high temperature, forming a dense interface structure, further improving the wear resistance and adhesion of the glaze layer, and improving the long-term wear resistance and mildew resistance of the glaze layer.
[0037] (4) The wear-resistant and mildew-proof ceramic tile provided by the present invention adopts a segmented sintering process. Through a reasonable heating rate and insulation time, the glaze layer material is fully melted and forms a stable bonding interface with the blank. At the same time, it avoids the defects of bubbles and cracks that may be caused by rapid heating, thereby ensuring the density and surface quality of the product. DETAILED DESCRIPTION
[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] In the present invention, the silver-loaded zirconium phosphate is purchased from Foshan Liyuan Chemical Co., Ltd., with a particle size of 1-2 μm and a silver content of 1.9-2.1%; the particle size of the calcium carbonate is 10-20 μm.
[0040] Example 1
[0041] A wear-resistant and mildew-proof tile comprises a body and a glaze layer attached to the body, wherein the glaze layer comprises the following raw materials in parts by weight:
[0042] 45 parts of silicon dioxide, 33 parts of aluminum oxide, 18 parts of modified titanium dioxide, 8 parts of barium carbonate, 8 parts of mullite, 7 parts of silver-loaded zirconium phosphate, 6 parts of potassium carbonate, 6 parts of sodium carbonate, 5 parts of limestone, 4 parts of sodium borate, 3 parts of zinc oxide, and 0.8 parts of sodium tripolyphosphate.
[0043] The green body comprises the following raw materials in parts by weight:
[0044] 43 parts of clay, 28 parts of kaolin, 18 parts of dolomite, 17 parts of quartz, 15 parts of potassium feldspar, 14 parts of red mud, 14 parts of mullite, 13 parts of diatomaceous earth, 8 parts of magnesium oxide, 7 parts of calcined talc, 3.5 parts of borax, and 2.5 parts of copper oxide.
[0045] Wherein, the preparation method of the modified interface agent comprises the following steps:
[0046] 13 g of aluminum phosphate was added to 150 g of glycerol aqueous solution (the mass fraction of glycerol was 55%), followed by 7 g of sodium dodecyl sulfate. After stirring evenly, 6 g of dimethyl allyl malonate, 7 g of aluminum acetylacetonate, 9 g of tetrapropyl zirconate, and 0.7 g of dibenzoyl peroxide were added. Stirring was continued for 28 min to obtain the modified interface agent.
[0047] The preparation method of the modified titanium dioxide comprises the following steps:
[0048] S1. Add 35 g of calcium carbonate to 780 mL of ethanol aqueous solution (the volume ratio of ethanol to water is 7.5:2.5), then add 85 g of tetrabutyl titanate and 55 g of 25% ammonia water, and hydrothermally react at 125° C. for 7 h. After the reaction is completed, filter, wash and dry. The solid product is calcined at 650° C. for 1.5 h, then added to 500 mL of 5% dilute hydrochloric acid solution, immersed for 25 min, then filtered, washed and dried to obtain porous titanium dioxide;
[0049] S2, adding 100g of porous titanium dioxide in step S1 to 1100g of deionized water, then adding 35g of zinc nitrate, 20g of cerium nitrate, and 15g of zirconium oxychloride, stirring evenly, adding 10% ammonia water to adjust the pH to 10, stirring and reacting at 63°C for 3.5h, filtering, washing, and drying after the reaction is completed, and calcining at 530°C for 2.5h to obtain composite titanium dioxide;
[0050] S3. Add 100 g of the composite titanium dioxide in step S2 to 900 g of ethanol aqueous solution (the volume ratio of ethanol to water is 7.5:2.5), then add 12 g of vinyltriethoxysilane, and react at 55° C. for 2.5 h. After the reaction is completed, filter, wash, and dry to obtain modified titanium dioxide.
[0051] A method for preparing wear-resistant and mildew-proof tiles comprises the following steps:
[0052] (1) Preparation of ceramic tile blanks: weigh raw materials according to the formula, mix clay, kaolin, dolomite, quartz, potassium feldspar, red mud, mullite, diatomaceous earth, magnesium oxide, calcined talc, borax, and copper oxide evenly, add 38% of water by weight of the total ingredients of the blank to prepare a slurry, ball mill for 3.5 hours, sieve, deaerate, press mold at 45 MPa, and then dry at 105° C. for 5 hours to obtain ceramic tile blanks;
[0053] (2) preparing glaze layer materials: weighing raw materials according to the formula, mixing silicon dioxide, aluminum oxide, modified titanium dioxide, barium carbonate, mullite, silver-loaded zirconium phosphate, potassium carbonate, sodium carbonate, limestone, sodium borate, zinc oxide, and sodium tripolyphosphate, adding water accounting for 72% of the total weight of the glaze layer ingredients to prepare a glaze slurry, ball milling for 8 hours, and passing the glaze slurry through a 325-mesh sieve after milling to obtain a glaze layer material;
[0054] (3) Apply the modified interface agent evenly on the dried tile body, with a coating amount of 110g / m 2, preheat at 55°C for 25 minutes, then use the glaze spraying process to spray the prepared glaze layer material on the tile body, control the thickness to be 0.5mm, and heat treat at 115°C for 50 minutes; place the glazed tiles in a roller kiln for sintering, the sintering process is pre-fired at 450°C for 35 minutes, then heat-raised to 1180°C at a rate of 7°C / min, kept warm for 45 minutes, and finally cooled to obtain the wear-resistant and mildew-proof tiles.
[0055] Example 2
[0056] A wear-resistant and mildew-proof tile comprises a body and a glaze layer attached to the body, wherein the glaze layer comprises the following raw materials in parts by weight:
[0057] 40 parts of silicon dioxide, 30 parts of aluminum oxide, 15 parts of modified titanium dioxide, 6 parts of barium carbonate, 6 parts of mullite, 5 parts of silver-loaded zirconium phosphate, 4 parts of potassium carbonate, 4 parts of sodium carbonate, 3 parts of limestone, 3 parts of sodium borate, 2 parts of zinc oxide, and 0.5 parts of sodium tripolyphosphate.
[0058] The green body comprises the following raw materials in parts by weight:
[0059] 40 parts of clay, 25 parts of kaolin, 15 parts of dolomite, 15 parts of quartz, 12 parts of potassium feldspar, 12 parts of red mud, 12 parts of mullite, 10 parts of diatomaceous earth, 6 parts of magnesium oxide, 5 parts of calcined talc, 3 parts of borax, and 2 parts of copper oxide.
[0060] Wherein, the preparation method of the modified interface agent comprises the following steps:
[0061] 10g of aluminum phosphate is added to 130g of glycerol aqueous solution (the mass fraction of glycerol is 50%), followed by adding 5g of sodium dodecyl sulfate, stirring evenly, adding 2g of dimethyl allyl malonate, 6g of aluminum acetylacetonate, 7g of tetrapropyl zirconate, and 0.5g of dibenzoyl peroxide, and stirring is continued for 20min to obtain the modified interface agent.
[0062] The preparation method of the modified titanium dioxide comprises the following steps:
[0063] S1. Add 30 g of calcium carbonate to 700 mL of ethanol aqueous solution (the volume ratio of ethanol to water is 7:3), then add 80 g of tetrabutyl titanate and 50 g of 20% ammonia water, and hydrothermally react at 120° C. for 8 h. After the reaction is completed, filter, wash and dry. The solid product is calcined at 600° C. for 2 h, then added to 500 mL of 5% dilute hydrochloric acid solution, immersed for 20 min, then filtered, washed and dried to obtain porous titanium dioxide;
[0064] S2, adding 100g of porous titanium dioxide in step S1 to 1000g of deionized water, then adding 30g of zinc nitrate, 15g of cerium nitrate, and 10g of zirconium oxychloride, stirring evenly, adding 10% ammonia water to adjust the pH to 9, stirring and reacting at 60°C for 4h, filtering, washing, and drying after the reaction is completed, and calcining at 500°C for 3h to obtain composite titanium dioxide;
[0065] S3. Add 100 g of the composite titanium dioxide in step S2 to 900 g of ethanol aqueous solution (the volume ratio of ethanol to water is 7:3), then add 9 g of vinyltriethoxysilane, and react at 50° C. for 3 h. After the reaction is completed, filter, wash, and dry to obtain modified titanium dioxide.
[0066] A method for preparing wear-resistant and mildew-proof tiles comprises the following steps:
[0067] (1) Preparation of ceramic tile blanks: weigh raw materials according to the formula, mix clay, kaolin, dolomite, quartz, potassium feldspar, red mud, mullite, diatomaceous earth, magnesium oxide, calcined talc, borax, and copper oxide evenly, add 35% of water by weight of the total ingredients of the blank to prepare a slurry, ball mill for 3 h, sieve, deaerate, press mold at 40 MPa, and then dry at 100° C. for 6 h to obtain ceramic tile blanks;
[0068] (2) preparing glaze layer materials: weighing raw materials according to the formula, mixing silicon dioxide, aluminum oxide, modified titanium dioxide, barium carbonate, mullite, silver-loaded zirconium phosphate, potassium carbonate, sodium carbonate, limestone, sodium borate, zinc oxide, and sodium tripolyphosphate, adding water accounting for 70% of the total weight of the glaze layer ingredients to prepare a glaze slurry, ball milling for 7 hours, and passing the glaze slurry through a 325-mesh sieve after milling to obtain a glaze layer material;
[0069] (3) Apply the modified interface agent evenly on the dried tile body, with a coating amount of 110g / m 2 , preheat at 50°C for 30 minutes, then use the glaze spraying process to spray the prepared glaze layer material on the tile body, control the thickness to be 0.5mm, and heat treat at 110°C for 60 minutes; place the glazed tiles in a roller kiln for sintering, the sintering process is pre-fired at 400°C for 40 minutes, then heated to 1150°C at a rate of 5°C / min, kept warm for 50 minutes, and finally cooled to obtain the wear-resistant and mildew-proof tiles.
[0070] Example 3
[0071] A wear-resistant and mildew-proof tile comprises a body and a glaze layer attached to the body, wherein the glaze layer comprises the following raw materials in parts by weight:
[0072] 50 parts of silicon dioxide, 35 parts of aluminum oxide, 20 parts of modified titanium dioxide, 10 parts of barium carbonate, 10 parts of mullite, 8 parts of silver-loaded zirconium phosphate, 8 parts of potassium carbonate, 8 parts of sodium carbonate, 7 parts of limestone, 5 parts of sodium borate, 4 parts of zinc oxide, and 1 part of sodium tripolyphosphate.
[0073] The green body comprises the following raw materials in parts by weight:
[0074] 45 parts of clay, 30 parts of kaolin, 20 parts of dolomite, 20 parts of quartz, 17 parts of potassium feldspar, 16 parts of red mud, 16 parts of mullite, 15 parts of diatomaceous earth, 9 parts of magnesium oxide, 8 parts of calcined talc, 4 parts of borax, and 3 parts of copper oxide.
[0075] Wherein, the preparation method of the modified interface agent comprises the following steps:
[0076] 15g of aluminum phosphate is added to 60g of glycerol aqueous solution (the mass fraction of glycerol is 60%), followed by adding 9g of sodium dodecyl sulfate, stirring evenly, adding 4g of dimethyl allyl malonate, 8g of aluminum acetylacetonate, 11g of tetrapropyl zirconate, and 0.8g of dibenzoyl peroxide, and stirring is continued for 30min to obtain the modified interface agent.
[0077] The preparation method of the modified titanium dioxide comprises the following steps:
[0078] S1. Add 40g of calcium carbonate to 800mL of ethanol aqueous solution (the volume ratio of ethanol to water is 8:2), then add 90g of tetrabutyl titanate and 60g of 25% ammonia water, and hydrothermally react at 130°C for 5h. After the reaction is completed, filter, wash and dry. The solid product is roasted at 700°C for 1h, then added to 500mL of 5% dilute hydrochloric acid solution, immersed for 30min, then filtered, washed and dried to obtain porous titanium dioxide;
[0079] S2, adding 100g of porous titanium dioxide in step S1 to 1200g of deionized water, then adding 40g of zinc nitrate, 25g of cerium nitrate, and 20g of zirconium oxychloride, stirring evenly, adding 10% ammonia water to adjust the pH to 10, stirring and reacting at 65°C for 3h, filtering, washing, and drying after the reaction is completed, and calcining at 550°C for 2h to obtain composite titanium dioxide;
[0080] S3. Add 100 g of the composite titanium dioxide in step S2 to 900 g of ethanol aqueous solution (the volume ratio of ethanol to water is 8:2), then add 14 g of vinyltriethoxysilane, and react at 60° C. for 2 h. After the reaction is completed, filter, wash, and dry to obtain modified titanium dioxide.
[0081] A method for preparing wear-resistant and mildew-proof tiles comprises the following steps:
[0082] (1) Preparation of ceramic tile blanks: weigh raw materials according to the formula, mix clay, kaolin, dolomite, quartz, potassium feldspar, red mud, mullite, diatomaceous earth, magnesium oxide, calcined talc, borax, and copper oxide evenly, add 40% water of the total mass of the blank ingredients to prepare a slurry, ball mill for 4 hours, sieve, deaerate, press and form at 40-50 MPa, and then dry at 110° C. for 4 hours to obtain ceramic tile blanks;
[0083] (2) preparing glaze layer materials: weighing raw materials according to the formula, mixing silicon dioxide, aluminum oxide, modified titanium dioxide, barium carbonate, mullite, silver-loaded zirconium phosphate, potassium carbonate, sodium carbonate, limestone, sodium borate, zinc oxide, and sodium tripolyphosphate, adding 75% of water by weight of the total ingredients of the glaze layer to prepare a glaze slurry, ball milling for 9 hours, and passing the glaze slurry through a 325-mesh sieve after milling to obtain a glaze layer material;
[0084] (3) Apply the modified interface agent evenly on the dried tile body, with a coating amount of 110g / m 2 , preheat at 60°C for 20 minutes, then use the glaze spraying process to spray the prepared glaze layer material on the tile body, control the thickness to be 0.5mm, and heat treat at 120°C for 40 minutes; place the glazed tiles in a roller kiln for sintering, the sintering process is pre-fired at 500°C for 30 minutes, then heat raised to 1200°C at a rate of 8°C / min, keep warm for 40 minutes, and finally cool to obtain the wear-resistant and mildew-proof tiles.
[0085] Comparative Example 1
[0086] A wear-resistant and mildew-proof tile comprises a body and a glaze layer attached to the body, wherein the glaze layer comprises the following raw materials in parts by weight:
[0087] 45 parts of silicon dioxide, 33 parts of aluminum oxide, 18 parts of porous titanium dioxide, 8 parts of barium carbonate, 8 parts of mullite, 7 parts of silver-loaded zirconium phosphate, 6 parts of potassium carbonate, 6 parts of sodium carbonate, 5 parts of limestone, 4 parts of sodium borate, 3 parts of zinc oxide, and 0.8 parts of sodium tripolyphosphate.
[0088] The green body comprises the following raw materials in parts by weight:
[0089] 43 parts of clay, 28 parts of kaolin, 18 parts of dolomite, 17 parts of quartz, 15 parts of potassium feldspar, 14 parts of red mud, 14 parts of mullite, 13 parts of diatomaceous earth, 8 parts of magnesium oxide, 7 parts of calcined talc, 3.5 parts of borax, and 2.5 parts of copper oxide.
[0090] Wherein, the preparation method of the modified interface agent comprises the following steps:
[0091] 13 g of aluminum phosphate was added to 150 g of glycerol aqueous solution (the mass fraction of glycerol was 55%), followed by 7 g of sodium dodecyl sulfate. After stirring evenly, 6 g of dimethyl allyl malonate, 7 g of aluminum acetylacetonate, 9 g of tetrapropyl zirconate, and 0.7 g of dibenzoyl peroxide were added. Stirring was continued for 28 min to obtain the modified interface agent.
[0092] The method for preparing porous titanium dioxide comprises the following steps:
[0093] S1. Add 35g of calcium carbonate to 780mL of ethanol aqueous solution (the volume ratio of ethanol to water is 7.5:2.5), then add 85g of tetrabutyl titanate and 55g of 25% ammonia water, and hydrothermally react at 125°C for 7h. After the reaction is completed, filter, wash and dry. Roast the solid product at 650°C for 1.5h, then add 500mL of 5% dilute hydrochloric acid solution, soak for 25min, and then filter, wash and dry to obtain porous titanium dioxide.
[0094] A method for preparing wear-resistant and mildew-proof tiles comprises the following steps:
[0095] (1) Preparation of ceramic tile blanks: weigh raw materials according to the formula, mix clay, kaolin, dolomite, quartz, potassium feldspar, red mud, mullite, diatomaceous earth, magnesium oxide, calcined talc, borax, and copper oxide evenly, add 38% of water by weight of the total ingredients of the blank to prepare a slurry, ball mill for 3.5 hours, sieve, deaerate, press mold at 45 MPa, and then dry at 105° C. for 5 hours to obtain ceramic tile blanks;
[0096] (2) preparing glaze layer materials: weighing raw materials according to the formula, mixing silicon dioxide, aluminum oxide, porous titanium dioxide, barium carbonate, mullite, silver-loaded zirconium phosphate, potassium carbonate, sodium carbonate, limestone, sodium borate, zinc oxide, and sodium tripolyphosphate, adding water accounting for 72% of the total weight of the glaze layer ingredients to prepare a glaze slurry, ball milling for 8 hours, and passing the glaze slurry through a 325-mesh sieve after milling to obtain a glaze layer material;
[0097] (3) Apply the modified interface agent evenly on the dried tile body, with a coating amount of 110g / m 2 , preheat at 55°C for 25 minutes, then use the glaze spraying process to spray the prepared glaze layer material on the tile body, control the thickness to be 0.5mm, and heat treat at 115°C for 50 minutes; place the glazed tiles in a roller kiln for sintering, the sintering process is pre-fired at 450°C for 35 minutes, then heat-raised to 1180°C at a rate of 7°C / min, kept warm for 45 minutes, and finally cooled to obtain the wear-resistant and mildew-proof tiles.
[0098] Compared with Example 1, in this comparative example, porous titanium dioxide is added into the glaze layer material.
[0099] Comparative Example 2
[0100] A wear-resistant and mildew-proof tile comprises a body and a glaze layer attached to the body, wherein the glaze layer comprises the following raw materials in parts by weight:
[0101] 45 parts of silicon dioxide, 33 parts of aluminum oxide, 18 parts of modified titanium dioxide, 8 parts of barium carbonate, 8 parts of mullite, 7 parts of silver-loaded zirconium phosphate, 6 parts of potassium carbonate, 6 parts of sodium carbonate, 5 parts of limestone, 4 parts of sodium borate, 3 parts of zinc oxide, and 0.8 parts of sodium tripolyphosphate.
[0102] The green body comprises the following raw materials in parts by weight:
[0103] 43 parts of clay, 28 parts of kaolin, 18 parts of dolomite, 17 parts of quartz, 15 parts of potassium feldspar, 14 parts of red mud, 14 parts of mullite, 13 parts of diatomaceous earth, 8 parts of magnesium oxide, 7 parts of calcined talc, 3.5 parts of borax, and 2.5 parts of copper oxide.
[0104] Wherein, the preparation method of the modified interface agent comprises the following steps:
[0105] 13 g of aluminum phosphate was added to 150 g of glycerol aqueous solution (the mass fraction of glycerol was 55%), followed by adding 7 g of sodium dodecyl sulfate, stirring evenly, then adding 7 g of aluminum acetylacetonate, and continuing stirring for 28 min to obtain the modified interface agent.
[0106] The preparation method of the modified titanium dioxide comprises the following steps:
[0107] S1. Add 35 g of calcium carbonate to 780 mL of ethanol aqueous solution (the volume ratio of ethanol to water is 7.5:2.5), then add 85 g of tetrabutyl titanate and 55 g of 25% ammonia water, and hydrothermally react at 125° C. for 7 h. After the reaction is completed, filter, wash and dry. The solid product is calcined at 650° C. for 1.5 h, then added to 500 mL of 5% dilute hydrochloric acid solution, immersed for 25 min, then filtered, washed and dried to obtain porous titanium dioxide;
[0108] S2, adding 100g of porous titanium dioxide in step S1 to 1100g of deionized water, then adding 35g of zinc nitrate, 20g of cerium nitrate, and 15g of zirconium oxychloride, stirring evenly, adding 10% ammonia water to adjust the pH to 10, stirring and reacting at 63°C for 3.5h, filtering, washing, and drying after the reaction is completed, and calcining at 530°C for 2.5h to obtain composite titanium dioxide;
[0109] S3. Add 100 g of the composite titanium dioxide in step S2 to 900 g of ethanol aqueous solution (the volume ratio of ethanol to water is 7.5:2.5), then add 12 g of vinyltriethoxysilane, and react at 55° C. for 2.5 h. After the reaction is completed, filter, wash, and dry to obtain modified titanium dioxide.
[0110] A method for preparing wear-resistant and mildew-proof tiles comprises the following steps:
[0111] (1) Preparation of ceramic tile blanks: weigh raw materials according to the formula, mix clay, kaolin, dolomite, quartz, potassium feldspar, red mud, mullite, diatomaceous earth, magnesium oxide, calcined talc, borax, and copper oxide evenly, add 38% of water by weight of the total ingredients of the blank to prepare a slurry, ball mill for 3.5 hours, sieve, deaerate, press mold at 45 MPa, and then dry at 105° C. for 5 hours to obtain ceramic tile blanks;
[0112] (2) preparing glaze layer materials: weighing raw materials according to the formula, mixing silicon dioxide, aluminum oxide, modified titanium dioxide, barium carbonate, mullite, silver-loaded zirconium phosphate, potassium carbonate, sodium carbonate, limestone, sodium borate, zinc oxide, and sodium tripolyphosphate, adding water accounting for 72% of the total weight of the glaze layer ingredients to prepare a glaze slurry, ball milling for 8 hours, and passing the glaze slurry through a 325-mesh sieve after milling to obtain a glaze layer material;
[0113] (3) Apply the modified interface agent evenly on the dried tile body, with a coating amount of 110g / m 2 , preheat at 55°C for 25 minutes, then use the glaze spraying process to spray the prepared glaze layer material on the tile body, control the thickness to be 0.5mm, and heat treat at 115°C for 50 minutes; place the glazed tiles in a roller kiln for sintering, the sintering process is pre-fired at 450°C for 35 minutes, then heat-raised to 1180°C at a rate of 7°C / min, kept warm for 45 minutes, and finally cooled to obtain the wear-resistant and mildew-proof tiles.
[0114] Compared with Example 1, dimethyl allyl malonate, tetrapropyl zirconate and dibenzoyl peroxide are not added to the modified interface agent of this comparative example.
[0115] Comparative Example 3
[0116] A wear-resistant and mildew-proof tile comprises a body and a glaze layer attached to the body, wherein the glaze layer comprises the following raw materials in parts by weight:
[0117] 45 parts of silicon dioxide, 33 parts of aluminum oxide, 18 parts of porous titanium dioxide, 8 parts of barium carbonate, 8 parts of mullite, 7 parts of silver-loaded zirconium phosphate, 6 parts of potassium carbonate, 6 parts of sodium carbonate, 5 parts of limestone, 4 parts of sodium borate, 3 parts of zinc oxide, and 0.8 parts of sodium tripolyphosphate.
[0118] The green body comprises the following raw materials in parts by weight:
[0119] 43 parts of clay, 28 parts of kaolin, 18 parts of dolomite, 17 parts of quartz, 15 parts of potassium feldspar, 14 parts of red mud, 14 parts of mullite, 13 parts of diatomaceous earth, 8 parts of magnesium oxide, 7 parts of calcined talc, 3.5 parts of borax, and 2.5 parts of copper oxide.
[0120] Wherein, the preparation method of the modified interface agent comprises the following steps:
[0121] 13 g of aluminum phosphate was added to 150 g of glycerol aqueous solution (the mass fraction of glycerol was 55%), followed by adding 7 g of sodium dodecyl sulfate, stirring evenly, then adding 7 g of aluminum acetylacetonate, and continuing stirring for 28 min to obtain the modified interface agent.
[0122] The method for preparing porous titanium dioxide comprises the following steps:
[0123] Add 35g of calcium carbonate to 780mL of ethanol aqueous solution (the volume ratio of ethanol to water is 7.5:2.5), then add 85g of tetrabutyl titanate and 55g of 25% ammonia water, and hydrothermally react at 125°C for 7h. After the reaction is completed, filter, wash and dry. The solid product is calcined at 650°C for 1.5h, then added to 500mL of 5% dilute hydrochloric acid solution, immersed for 25min, and then filtered, washed and dried to obtain porous titanium dioxide.
[0124] A method for preparing wear-resistant and mildew-proof tiles comprises the following steps:
[0125] (1) Preparation of ceramic tile blanks: weigh raw materials according to the formula, mix clay, kaolin, dolomite, quartz, potassium feldspar, red mud, mullite, diatomaceous earth, magnesium oxide, calcined talc, borax, and copper oxide evenly, add 38% of water by weight of the total ingredients of the blank to prepare a slurry, ball mill for 3.5 hours, sieve, deaerate, press mold at 45 MPa, and then dry at 105° C. for 5 hours to obtain ceramic tile blanks;
[0126] (2) preparing glaze layer materials: weighing raw materials according to the formula, mixing silicon dioxide, aluminum oxide, porous titanium dioxide, barium carbonate, mullite, silver-loaded zirconium phosphate, potassium carbonate, sodium carbonate, limestone, sodium borate, zinc oxide, and sodium tripolyphosphate, adding water accounting for 72% of the total weight of the glaze layer ingredients to prepare a glaze slurry, ball milling for 8 hours, and passing the glaze slurry through a 325-mesh sieve after milling to obtain a glaze layer material;
[0127] (3) Apply the modified interface agent evenly on the dried tile body, with a coating amount of 110g / m 2, preheat at 55°C for 25 minutes, then use the glaze spraying process to spray the prepared glaze layer material on the tile body, control the thickness to be 0.5mm, and heat treat at 115°C for 50 minutes; place the glazed tiles in a roller kiln for sintering, the sintering process is pre-fired at 450°C for 35 minutes, then heat-raised to 1180°C at a rate of 7°C / min, kept warm for 45 minutes, and finally cooled to obtain the wear-resistant and mildew-proof tiles.
[0128] Compared with Example 1, in this comparative example, porous titanium dioxide is added to the glaze layer material, and dimethyl allyl malonate, tetrapropyl zirconate and dibenzoyl peroxide are not added to the modified interface agent.
[0129] The ceramic tiles prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests. According to JC / T897-2014 "Antibacterial Performance of Antibacterial Ceramic Products", the antibacterial rate of Staphylococcus aureus of the ceramic tiles was tested, and the greater the antibacterial rate, the better the antibacterial property of the ceramic tiles; the antibacterial persistence was tested by the following method: the ceramic tile surface was scrubbed with sodium hypochlorite having a mass concentration of 10%, and the scrubbing frequency was 1500 times. After the scrubbing was completed, the antibacterial rate of Staphylococcus aureus of the ceramic tiles was tested; the wear resistance of the glaze was tested according to GB / T 4100-2015, randomly take out 3 tiles and conduct friction and wear tests on the MMS-1G high-speed pin-disc friction and wear tester, record the wear amount, and detect the wear resistance of the tiles; glaze adhesion performance test: the American standard test method for measuring adhesion by tape test (D3359-08) was used for testing. The test steps are as follows: cut a 5×5mm grid with a knife in a test area of 125mm2, place the center of the tape on the grid, and smooth the center of the grid with your fingers. Then after 90±30s, grab the free end, tear off the tape, and tear off the tape quickly (without shaking) at an angle as close to 180° as possible. Finally, use a magnifying glass to check the test area, and determine the material drop ratio by comparing it with the material attachment area before the test. The whole experiment was repeated three times. The test results are shown in Table 1 below:
[0130] Table 1 Test results of different groups of ceramic tiles
[0131] Group Initial antibacterial rate (%) Antibacterial rate after 1500 washings (%) Wear amount (mg) Glaze adhesion Example 1 99.68 99.37 0.35 5B Example 2 99.32 99.05 0.48 5B Example 3 99.46 99.12 0.39 5B Comparative Example 1 99.18 93.82 1.06 4B Comparative Example 2 99.53 95.11 0.62 4B Comparative Example 3 99.12 91.25 1.29 3B
[0132] It can be seen from Table 1 above that the wear-resistant and mildew-proof ceramic tiles provided by the present invention have good initial antibacterial properties, and the antibacterial rate does not decrease significantly after washing 1500 times, indicating that it has a long-lasting antibacterial effect. At the same time, it also has good wear resistance and glaze adhesion, and has good application prospects.
[0133] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A wear-resistant and mildew-proof tile, comprising a body and a glaze layer attached to the body, characterized in that: The wear-resistant and mildew-proof ceramic tile is obtained by first coating the surface of the green body with a modified interface agent and then glazing it; Wherein, the glaze layer comprises the following raw materials by weight: 40-50 parts of silicon dioxide, 30-35 parts of aluminum oxide, 15-20 parts of modified titanium dioxide, 6-10 parts of barium carbonate, 6-10 parts of mullite, 5-8 parts of silver-loaded zirconium phosphate, 4-8 parts of potassium carbonate, 4-8 parts of sodium carbonate, 3-7 parts of limestone, 3-5 parts of sodium borate, 2-4 parts of zinc oxide, and 0.5-1 parts of sodium tripolyphosphate. The green body comprises the following raw materials in parts by weight: 40-45 parts of clay, 25-30 parts of kaolin, 15-20 parts of dolomite, 15-20 parts of quartz, 12-17 parts of potassium feldspar, 12-16 parts of red mud, 12-16 parts of mullite, 10-15 parts of diatomaceous earth, 6-9 parts of magnesium oxide, 5-8 parts of calcined talc, 3-4 parts of borax, and 2-3 parts of copper oxide.
2. The wear-resistant and mildew-proof ceramic tile according to claim 1, characterized in that: The glaze layer comprises the following raw materials, by weight: 45-50 parts of silicon dioxide, 32-35 parts of aluminum oxide, 17-20 parts of modified titanium dioxide, 6-8 parts of barium carbonate, 6-8 parts of mullite, 6-8 parts of silver-loaded zirconium phosphate, 4-6 parts of potassium carbonate, 4-6 parts of sodium carbonate, 4-6 parts of limestone, 3-4 parts of sodium borate, 2-3 parts of zinc oxide, and 0.5-0.8 parts of sodium tripolyphosphate.
3. The wear-resistant and mildew-proof ceramic tile according to claim 1, characterized in that: The thickness of the glaze layer is 0.3-0.5 mm.
4. The wear-resistant and mildew-proof ceramic tile according to claim 1, characterized in that: The preparation method of the modified interface agent comprises the following steps: Aluminum phosphate is added to the glycerol aqueous solution, followed by sodium dodecyl sulfate, and after stirring evenly, dimethyl allyl malonate, aluminum acetylacetonate, tetrapropyl zirconate, and dibenzoyl peroxide are added, and stirring is continued for 20-30 minutes to obtain the modified interface agent.
5. The wear-resistant and mildew-proof ceramic tile according to claim 4, characterized in that: The stirring temperature is 30-40° C., the mass fraction of glycerol in the glycerol aqueous solution is 50-60%, and the mass ratio of the aluminum phosphate, glycerol aqueous solution, sodium lauryl sulfate, dimethyl allyl malonate, aluminum acetylacetonate, tetrapropyl zirconate, and dibenzoyl peroxide is 10-15:130-160:5-9:2-4:6-8:7-11:0.5-0.
8.
6. The wear-resistant and mildew-proof ceramic tile according to claim 1, characterized in that: The preparation method of the modified titanium dioxide comprises the following steps: S1. Add calcium carbonate to an ethanol aqueous solution, then add tetrabutyl titanate and ammonia water to carry out a hydrothermal reaction. After the reaction is completed, filter, wash, dry, and roast. Add to a dilute hydrochloric acid solution, soak for 20-30 minutes, then filter, wash, and dry to obtain porous titanium dioxide. S2, adding the porous titanium dioxide prepared in step S1 into deionized water, and then adding zinc nitrate, cerium nitrate and zirconium oxychloride, stirring evenly, adding ammonia water to adjust the pH to 9-10, stirring to react, filtering, washing, drying and calcining after the reaction is completed to obtain composite titanium dioxide; S3, adding the composite titanium dioxide in step S2 into an ethanol aqueous solution, and then adding vinyltriethoxysilane, reacting at 50-60° C. for 2-3 hours, filtering, washing, and drying after the reaction is completed to obtain modified titanium dioxide.
7. The wear-resistant and mildew-proof ceramic tile according to claim 6, characterized in that: In step S1, the volume ratio of ethanol to water in the ethanol aqueous solution is 7-8:2-3, the mass ratio of calcium carbonate, tetrabutyl titanate and ammonia water is 30-40:80-90:50-60, the mass fraction of ammonia water is 20-25%, the temperature of the hydrothermal reaction is 120-130°C, the time is 5-8h, and the calcination temperature is 600-700°C, and the time is 1-2h.
8. The wear-resistant and mildew-proof ceramic tile according to claim 6, characterized in that: In step S2, the mass ratio of porous titanium dioxide, deionized water, zinc nitrate, cerium nitrate and zirconium oxychloride is 100:1000-1200:30-40:15-25:10-20, the stirring reaction temperature is 60-65°C, the time is 3-4h, and the calcination temperature is 500-550°C, and the time is 2-3h.
9. The wear-resistant and mildew-proof ceramic tile according to claim 6, characterized in that: The mass ratio of the composite titanium dioxide and vinyltriethoxysilane in step S3 is 100:9-14.
10. A method for preparing the wear-resistant and mildew-proof ceramic tile according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Preparation of ceramic tile blanks: weigh raw materials according to the formula, mix clay, kaolin, dolomite, quartz, potassium feldspar, red mud, mullite, diatomaceous earth, magnesium oxide, calcined talc, borax, and copper oxide evenly, add 35-40% of water by weight of the total ingredients of the blank to prepare a slurry, ball mill for 3-4 hours, sieve, degas, press and form at 40-50 MPa, and then dry at 100-110° C. to obtain ceramic tile blanks; (2) preparing glaze layer materials: weighing raw materials according to the formula, mixing silicon dioxide, aluminum oxide, modified titanium dioxide, barium carbonate, mullite, silver-loaded zirconium phosphate, potassium carbonate, sodium carbonate, limestone, sodium borate, zinc oxide, and sodium tripolyphosphate, adding 70-75% of water by weight of the total ingredients of the glaze layer to prepare a glaze slurry, ball milling for 7-9 hours, and passing the glaze slurry through a 325-mesh sieve after milling to obtain a glaze layer material; (3) Apply the modified interface agent evenly on the dry tile body, with a coating amount of 100-120g / m 2 , preheat at 50-60℃ for 20-30min, then use the glaze spraying process to spray the prepared glaze layer material on the tile body, and heat treat at 110-120℃ for 40-60min; place the glazed tiles in a roller kiln for sintering, the sintering process is pre-firing at 400-500℃ for 30-40min, then heating to 1150-1200℃ at a rate of 5-8℃ / min, keeping warm for 40-50min, and finally cooling to obtain the wear-resistant and mildew-proof tiles.
Citation Information
Patent Citations
Anti-bacterial ceramic tile and preparation method thereof
CN109016098A
Anti-slip wear-resistant antibacterial ceramic tile and preparation method thereof
CN117049782A
Cited By
Steel plate enamel low-temperature acid-resistant ground coat free of fluoride salt and nitrate as well as preparation method and application of steel plate enamel low-temperature acid-resistant ground coat
CN121159096A
Fluoride-free and nitrate-free steel enamel low-temperature acid-resistant ground coat and preparation method and application thereof
CN121159096B
Cast iron enamel high-temperature ground coat free of fluoride salt and nitrate as well as preparation method and application of ground coat
CN121159103A